2014
DOI: 10.1111/epi.12868
|View full text |Cite
|
Sign up to set email alerts
|

Gelastic seizures: Incidence, clinical andEEGfeatures in adult patients undergoing video‐EEGtelemetry

Abstract: SUMMARYThis study aimed to determine clinical features of adult patients with gelastic seizures recorded on video -electroencephalography (EEG) over a 5-year period. We screened video-EEG telemetry reports for the occurrence of the term "gelastic" seizures, and assessed the semiology, EEG features, and duration of those seizures. Gelastic seizures were identified in 19 (0.8%) of 2,446 admissions. The presumed epileptogenic zone was in the hypothalamus in one third of the cases, temporal lobe epilepsy was diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 15 publications
2
30
1
1
Order By: Relevance
“…Gelastic seizures are mainly attributed to hypothalamic hamartomas; however it is also reported that epileptogenic zone may be in the hypothalamus as well as in the temporal lobe. In some cases, this type of seizure may be also a manifestation of epilepsy of other localizations or multifocal epilepsy [4, 5]. The phenomenology of seizures experienced by our patient (concomitant visual and auditory hallucination) suggests involvement of other regions, such as temporal lobe.…”
Section: Discussionmentioning
confidence: 69%
“…Gelastic seizures are mainly attributed to hypothalamic hamartomas; however it is also reported that epileptogenic zone may be in the hypothalamus as well as in the temporal lobe. In some cases, this type of seizure may be also a manifestation of epilepsy of other localizations or multifocal epilepsy [4, 5]. The phenomenology of seizures experienced by our patient (concomitant visual and auditory hallucination) suggests involvement of other regions, such as temporal lobe.…”
Section: Discussionmentioning
confidence: 69%
“…Following an intracarotid amobarbital test, a successful right ATL was performed. In the largest case series of GS (Kovac et al, 2015), two out of 19 patients underwent ATL for a temporal epileptogenic zone resulting in seizure freedom. Gutierrez et al (2016) Engel Class III in one (5.6%); and Engel Class IV in two (11.1%).…”
Section: Discussionmentioning
confidence: 99%
“…It is now recognized that they are not pathognomonic of HH and can be found in temporal or extratemporal, lesional or non-lesional epilepsy, mostly in adults [2], [3], [4]. However there is a growing body of evidence of such cases in children [5], [6].…”
Section: Discussionmentioning
confidence: 99%